Natural infections of Hyalomma species with Theileria annulata in Malatya region - Aktas, M; Dumanli, N (Scientific Technical Research Council Turkey, 2001)
This study was carried out to determine Hyalomma ticks and the natural infections of Hyalomma species with Theileria annulata in cattle and their shelters in Malatya province between May 1998 and January 1999. Selected areas in Malatya province were visited to collect ticks from cows and their shelters during the study. Salivary glands of Hyalomma species were dissected and thin films were prepared. The nymphs collected from cattle and their shelters were kept at 26 degreesC and 85% relative humidity. Unfed adults of Hyalom ma species taken from engorged nymphs and collected from shelters were kept at 37 degreesC and 85% relative humidity for at least five days, and then salivary glands were dissected. All films prepared from salivary glands were stained with Methylegreen/Pyronin stain and examined for T.annulata infection under microscope. A total of 1633 Hyalomma ticks were collected from cattle, and their species were determined and the numbers were as follows: Hyalomma anatolicum anatolicum 990 (60.6%), H.a.excavatum 485 (29.6%), H.detritum 155 (9.4%) and H.marginatum 3 (0.1%). From these ticks, 720 H.a.anatolicum, 258 H.a.excavatum and 87 H.detritum were dissected to determine the infection rates of T.annulata. The infection rates were found to be 12.4% for H.a.anatolicum, 7.8% for H.a.excavatum and 4.6% for H.detritum. Eighty-three out of 443 H.a.anatolicum collected from shelters were positive for T.annulata. Mean numbers of infected acini per infected male and female ticks from cattle were 9.2 and 15.4 in H.a.anatolicum, 4.0 and 6.8 in H.a.excavatum. in H.a.anatolicum collected from shelters, the above rates were 9.3 and 4.9, respectively. in male H.detritum collected from cattle, there were no infections.
Keywords: Theileria annulata; Hyalomma; salivary gland; cattle